Implementasi Model Pembelajaran Project Based Learning (PjBL) pada Mata Pelajaran IPAS Kelas III di SD No 1 Petang Badung - Ni Putu Ari Trisnayanti; I Nengah Lestawi; I Made Sukariawan (Lembaga Yasin AlSys, 2025)
An appropriate learning approach plays a strategic role in enhancing the quality of education, particularly in developing 21st-century skills. However, many educators still employ conventional methods that inadequately support active and meaningful learning. This study aims to: (1) identify the implementation of Project Based Learning (PjBL) in third-grade Natural and Social Sciences (IPAS) at SD No. 1 Petang Badung; (2) examine challenges and strategies for overcoming them; and (3) analyze the impact of PjBL on student learning outcomes. The study draws on constructivism (Jean Piaget), behaviorism (Ivan Petrovic Pavlov), and learning motivation (Abraham Maslow) theories. Data were collected through observation, interviews, and literature review, then analyzed descriptively using a qualitative approach. The findings indicate that the implementation of PjBL enhances teachers’ creativity in lesson planning and fosters student independence, responsibility, and active engagement. Despite challenges such as limited time and resources, corrective strategies proved effective in mitigating these obstacles. The study concludes that the PjBL model holds significant potential to optimize IPAS learning at the elementary education level, particularly in cultivating contextual and problem-solving learning skills.